METHODOLOGY FOR DETERMINING PARAMETERS OF DESIGN VEHICLE, TAKING INTO ACCOUNT CONDITIONS OF ARCTIC ZONE OF THE RUSSIAN FEDERATION - Shevtsova, Anastasia; Novikov, Aleksandr; Loktionova, Alina (Journal of Applied Engineering Science, 2022)
Over the past decades, the automotive market has been growing and developing rapidly. Vehicles are constantly modified: their geometric parameters (length, width, height, etc.) and dynamic parameters (power, acceleration speed, etc.) change. For the design and construction of the roadway, as well as subsequent calculations in the field of traffic management (flow saturation, mandatory control, etc.) in accordance with the regulatory documentation, geometric and dynamic parameters of the design vehicle are used, the parameters of which are determined on the basis of Soviet cars of the 80s. As a result of vehicles changes and modifications, it is necessary to update and perform additional calculations to determine the parameters of an improved design - calibrated vehicle. The main purpose of the study is to determine the parameters of the design – calibrated vehicle for performing calculations in the field of construction and traffic management. In the course of the research presented in this article, the analysis of statistical data regarding the best-selling light vehicles, as well as the variability of the geometric parameters of vehicles were determined. Based on all the completed tasks, the result of the work is determination of the design - calibrated vehicle for Arctic zone of the Russian Federation, which will be subsequently used for the design and construction of the roadway and calculations in the field of traffic management.
Keywords: traffic flow, saturation flow, heterogeneity, design vehicle, geometric parameters